Revealing Lakoff and Johnson’s Metaphors Portrayed in Laufey’s Song Lyrics in Listening Skill - Maimuna, Linta Wafdan Hidayah, Jaftiyatur Rohaniyah (Journal of Educational Studies, 2025)
This qualitative research, employing a case research approach, aims to provide a detailed description of the metaphors found in the lyrics of the song “Laufey” and to examine their relevance to listening comprehension in English language learning in Class XI-S6 at Miftahul Ulum Islamic High School in Bettet, Pamekasan. Data collection was conducted through observation, interviews, and documentation on January 25–26, 2026. This research explored student engagement and learning outcomes. The results indicate that there are 4 structural metaphors, 2 orientational metaphors, and 5 ontological metaphors in the lyrics of the song “Tough Luck.” There were 3 structural metaphors, 1 orientational metaphor, and 11 ontological metaphors in the lyrics of the song “Lover Girl.” There were 3 structural metaphors, 2 orientational metaphors, and 4 ontological metaphors in the lyrics of the song “Silver Lining.” There were 3 structural metaphors and 5 ontological metaphors in the lyrics of the song “Snow white.” The research results also indicate that understanding metaphors contributes positively to students’ listening skills. Therefore, incorporating metaphor analysis into listening activities can enhance students’ comprehension and engagement in learning English.